Evaluating university teaching and learning / Patricia J. Rogers - Rogers, Patricia J. (ACRULeT, Faculty of Education & UiTM Press, 2008)
This paper discusses ways to evaluate university teaching and learning in ways that improve the human capital of teachers and students. While evaluation of teaching and learning often focuses only on gathering and using student feedback with evaluation, there is of course a wide array of literally dozens of evaluation models, approaches and tools. These many alternatives offer the opportunity to match each particular situation with the most appropriate approach, providing there is some way of reviewing options and selecting the most relevant one. This paper sets out some of these different approaches to evaluation, and a guide to selecting which approach to evaluation should be used when, and how these might be useful not only to judge the quality of teaching and learning but to actually improve it.